2015
DOI: 10.3174/ajnr.a4325
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiologic Diagnosis of Minor Leak prior to Major SAH: Diagnosis by T1-FLAIR Mismatch

Abstract: BACKGROUND AND PURPOSE:In major SAH, the only method to diagnose a preceding minor leak is to ascertain the presence of a warning headache by interview; however, poor clinical condition and recall bias can cause inaccuracy. We devised a neuroradiologic method to diagnose previous minor leak in patients with SAH and attempted to determine whether warning (sentinel) headaches were associated with minor leaks before major SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…In 8 (24.2%) of 33 patients, SH was confirmed by either the patient or next of kin. Contrary to those of Oda et al, 1 the data from our study (Table) do not indicate any difference in radiologic bleeding characteristics, such as the presence of intracerebral hemorrhage and a higher rebleeding rate, or worse outcome in patients with SH. Nonetheless, mortality in our SH group was considerably high (37.5%), which once again renders distinguishing dangerous headache from innocuous headache on clinical grounds of paramount importance.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In 8 (24.2%) of 33 patients, SH was confirmed by either the patient or next of kin. Contrary to those of Oda et al, 1 the data from our study (Table) do not indicate any difference in radiologic bleeding characteristics, such as the presence of intracerebral hemorrhage and a higher rebleeding rate, or worse outcome in patients with SH. Nonetheless, mortality in our SH group was considerably high (37.5%), which once again renders distinguishing dangerous headache from innocuous headache on clinical grounds of paramount importance.…”
contrasting
confidence: 56%
“…ith great interest, we read the recent retrospective study of Oda et al 1 in the American Journal of Neuroradiology reporting a 33.9% incidence of minor leaks preceding aneurysmal subarachnoid hemorrhage (aSAH) confirmed by neuroradiologic methods, in which the authors found a much lower incidence of sentinel headache (SH) of 11% by patient interview. Our data from an ongoing Swiss prospective observational study (ClinicalTrials.gov identifier: NCT02129010) confirms that SH preceding aSAH is not by any means a rare phenomenon.…”
mentioning
confidence: 97%
“…Thus, we investigated the clinical features of patients with minor leak diagnosed by T1-FLAIR mismatch at the time of admission. 2 In our report, the incidence of patients whose history of warning headache was unknown by interview was high (46.5%, 59 of 127 cases). If we excluded these 59 patients whose history of warning headache was unknown by interview, warning headache determined by interview was 20.6% (14/68 patients).…”
mentioning
confidence: 55%
“…1,2 Therefore, the diagnosis of a minor leak by interview has poor accuracy, and it is difficult to grasp the clinical implications of an interviewdiagnosed minor leak. Thus, we investigated the clinical features of patients with minor leak diagnosed by T1-FLAIR mismatch at the time of admission.…”
mentioning
confidence: 99%
“…Images in which the CSF is suppressed with normal MRI examination are clinically commonly used. T2‐fluid‐attenuated inversion recovery (FLAIR), T1‐FLAIR, and white matter attenuated inversion recovery (WAIR) using double inversion recovery (DIR) are clinically significant representative sequences . The most important factor affecting contrast in these inversion recovery sequences is the T1 value.…”
Section: Introductionmentioning
confidence: 99%